The Absolute Perspective of the Personal Subject Hegel vs. Plato on Social Philosophy, Art, and Religion - Stekeler-Weithofer, Pirmin (Aesthetica Preprint, 2021)
Normally, we focus on objective matters, not on performances in apperception and judgment. High-level reflections on ourselves also tend to look sideways-on upon us as ‘individual objects’ – thus overlooking the basic facts of subjectivity, perspectivity, and temporal actuality in all our relations to the world. Hegel, who had realized this, is nevertheless widely attacked by defenders of ‘methodological individualism’ as defending a version of Platonic idealism and holism, claiming, allegedly, a higher existence of conceptual forms to empirical appearances. However, not Ancient Greek philosophy, but Christian religion and medieval art show us the absoluteness of subjectivity in performing a personal life, as Hegel argues in his criticism of Plato’s ‘collectivist’ and ‘conventional virtue, thus agreeing in part with Karl Popper. The highest dignity of human individuals thus results from free orientations at traditional and general wisdom, together with the insight, that all objectivity is relative to perspectival changes.